2009
DOI: 10.5194/cp-5-183-2009
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land surface properties and atmospheric CO<sub>2</sub> on the Last Glacial Maximum climate: a factor separation analysis

Abstract: Abstract. Many sensitivity studies have been carried out, using climate models of different degrees of complexity to test the climate response to Last Glacial Maximum boundary conditions. Here, instead of adding the forcings successively as in most previous studies, we applied the separation method of U. Stein et P. Alpert 1993, in order to determine rigorously the different contributions of the boundary condition modifications, and isolate the pure contributions from the interactions among the forcings. We ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
1
11
1
Order By: Relevance
“…The interaction between vegetation and atmosphere was found 415 to produce a warmer Miocene independent of CO2 by Knorr et al (2011). The interaction between vegetation and paleogeography produced a higher climate sensitivity in the modelled Miocene in Bradshaw et al (2015) and warming independent of CO2 by Henrot et al (2010) due to vegetation and lower-elevation topography. Land surface cover and increased northern transient eddy heat transport were found to result in polar warming in a modelled late Miocene in a fully coupled GCM by Micheels et al (2010).…”
Section: Climate Forcing and Co2 Levelsmentioning
confidence: 89%
See 1 more Smart Citation
“…The interaction between vegetation and atmosphere was found 415 to produce a warmer Miocene independent of CO2 by Knorr et al (2011). The interaction between vegetation and paleogeography produced a higher climate sensitivity in the modelled Miocene in Bradshaw et al (2015) and warming independent of CO2 by Henrot et al (2010) due to vegetation and lower-elevation topography. Land surface cover and increased northern transient eddy heat transport were found to result in polar warming in a modelled late Miocene in a fully coupled GCM by Micheels et al (2010).…”
Section: Climate Forcing and Co2 Levelsmentioning
confidence: 89%
“…Modelling efforts of the Miocene find that reconciling the combined constraints of ocean temperature, CO2 indicators and Antarctic ice sheet dynamics is a non-trivial task (Micheels et al, 2009;Henrot et al, 2010, Bradshaw et al, 2012Sijp et al, 2014), with vegetation seemingly integral in creating the Miocene climatic conditions (Henrot et al, 2010;Knorr et al, 2011;50 Krapp and Jungklaus, 2011;Micheels et al, 2011;Bradshaw et al, 2015) along with bathymetry, topography and CO2.…”
mentioning
confidence: 99%
“…Factor separation studies have found that ice sheets primarily cool climate through their low albedo, with increased elevation having a smaller effect (Henrot et al 2009;Yin et al 2009). Temperature anomalies are smaller away from the ice sheets, but the widespread cooling in this experiment, especially in the SH, differs from past ice sheet experiments (Broccoli and Manabe 1987;Henrot et al 2009;Yin et al 2009), which show areas of warming in the SH or ocean areas. Those studies used EMICs or had simple oceans, however, so the current results suggest that widespread cooling may be a more realistic response to expanded NH and Antarctic ice sheets.…”
Section: Climate Response Fingerprintsmentioning
confidence: 96%
“…A method of investigating linearity in more detail is the factor separation approach, in which climate simulations are driven by separate forcings as well as every combination of forcings for a given time period (Stein and Alpert 1993;Henrot et al 2009;Yin andBerger 2010, 2012). While effective, a pure factor separation approach requires many simulations to separate out the interactions between multiple forcings, which can become computationally expensive.…”
Section: Introductionmentioning
confidence: 99%
“…More recent applications have studied the planetary climate system's response to, for instance, vegetation-atmosphere feedback mechanisms (Dekker et al, 2010;Bathiany et al, 2012), large-scale changes in orography (Garreaud et al, 2010;Schmittner et al, 2011), and variations in astronomical forcings (Boschi et al, 2013;Linsenmeier et al, 2015). The model has also been used for paleoclimate studies (Henrot et al, 2009) and snowball Earth experiments (Spiegl et al, 2015;Lucarini et al, 2013). Some of these studies have also explored the existence of alternative equilibrium states of the planetary climate system, as well as the mechanisms behind potential state transitions (Dekker et al, 2010;Bathiany et al, 2012;Boschi et al, 2013;Linsenmeier et al, 2015).…”
Section: Model Descriptionmentioning
confidence: 99%